Analysis of the continuing education of a teaching hospital in the perception of the nursing team - Aline Togni Braga; Marta Maria Melleiro (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
The objectives of this study was to analyze the Service of Continuated Education (SCE) of a teaching hospital, from the perspective of the nursing team in the evaluative dimensions of structure, process and outcome and to identify factors involved in the activities undertaken by that service, based on the Donabedian model. This is an exploratory-descriptive study, carried through in a private teaching hospital. The data collection was conducted through a questionnaire, using a Likert scale. The treatment of the data was carried through a descriptive statistics using the Cronbach Alpha test. Analyzing the data, we observed that in the tree evaluated dimensions (structure, process and result) the nurse team had favorable perception relative to this service. However, the structure dimension received the highest favorability score, average of 4,56 (dp±4,97), with process dimension receiving the lower score of, average 40,44 (dp±5,11).